The substance of a speech made in the House of Commons by Will. Prynn of Lincolns-Inn, Esqre; on Munday the fourth of December, 1648. Touching the Ks answer to ye propositions of both Hs upon ye whole tr. whether they were satisfactory or not satisfactory. Wherein ye satisfactoriness of ye Ks answers to ye propositions for settlement of a firm and lasting peace, & future security of the subjects against all feared regal invasions, & encroachments whatsoever is clearly demonstrated. As likewise, that there is no other probable or possible way to settle a speedy firm & lasting peace, but by the Houses embracing and proceeding upon the large extraordinary concessions of the King in this tr, for ye kingdoms present weal & future security. And that the Armies remonstrance, Nov. 20. is a way to speedy and certain ruine; & a meer plot of the Jesuites to defame & destroy us. Put into writing, and published by him at the importunate request of divers Members, for the satisfaction of the whole kingdom, touching the Houses vote upon this debate. [electronic resource]
Summary goes here